Eventos extremos secos sobre a região Sudeste do Brasil durante a estação de verão - Bier, Anderson Augusto (2017)
It was carried out an identification of dry events and elaborated a dynamic and thermodynamic characterization of these ones, ocurring during summer over Southeast region of Brazil. Dry events were identified for a series of 35 years of daily interpolated precipitation data set. As the Southeast region has a wide territory, it presents different precipitation regimes, both spacially and temporally, and for this reason, it was divided into three subregions with homogeneous precipitation regimes through cluster analysis. This division has sectorized the Southeast region approximately in a meridional form, with the southernmost portion denominated R1, central portion R2 and the northernmost R3. It was evaluated two different temporal scales of dry events: synoptic (duration between 5 and 9 days) and intraseasonal (duration equal or greater than 10 days) for the R1, R2 and R3 regions separately. R3 presented the highest total number of dry events in both categories (synoptic and intraseasonal), followed by R2 and R1 respectively. It was computed composites, with reanalysis data for different meteorological variables, associated with synoptic and intraseasonal dry events for each of the three homogeneous precipitation regions. Concerning mean dynamic patterns associated with dry events, there were two main ones that drew the most attention. For synoptic dry events in R1, there was a predominance of a blocking ridge at various levels of the atmosphere over the entire southern portion of South America, diverting the transient systems towards the more central portions of the Atlantic Ocean. While for the rest of the dry (synoptic and intraseasonal) classes of events and for the different homogeneous regions of precipitation (R1, R2 and R3), dry events appeared to be more associated with a blocking high centered on the South and Southeast regions of Brazil. Some other characteristics found were: in all classes of dry events, it was noticed in the average outgoing longwave radiation (OLR) fields, a precipitation dipole indicative between the concerned region and the Plata Basin (Uruguay, northern Argentina, southern Paraguay and southern Brazil). For intraseasonal dry events over R1 and R2, positive rainfall anomalies were also detected over a wide area of Amazon, whereas in the R1 synoptic dry events was noticed the presence of rainfall over Northeast region of Brazil. The increase in precipitation over the Plata basin was generally associated with the intensification of the South America low-level jet east of the Andes, caused by the intrusion of a low-level anticyclonic anomaly between the coasts of the South and Southeast regions of Brazil, providing anomalous easterly winds over the Southeast and anomalous westerly winds over the Plata basin. For all dry events, except for the synoptic events in R1, at high levels of the troposphere, an anticyclonic anomaly was observed on the South of Brazil, in the same way providing anomalous easterly winds on the Southeast, whereas over Plata mouth (border between Uruguay and Argentina), anomalous westerly winds were observed, on a region that climatologically occurs the Upper Tropospheric Jet Streams, which was intensified by the anomalous westerly winds, contributing to the convection that are typically observed in the equatorial Upper Tropospheric Jet entrance. The increase in the convective activity over the Plata basin and its absence over the Southeast region of Brazil, led to an anomalous displacement to the south of the meteorological systems that are characteristical in high levels of the troposphere during the South American summer, such as the Bolivian High and the high level cyclonic vortex of the Northeast of Brazil. The composites associated with the intraseasonal dry events occurring during the 2013/14 and 2014/15 summer, when there was a large repercussion of the rainfall scarcity on the Southeast region, were similar to those described above, but the anomalies in practically all the dynamic and thermodynamic fields were more prominent.